2019
DOI: 10.1039/c8dt05048a
|View full text |Cite
|
Sign up to set email alerts
|

Hexanuclear 3d–4f complexes as efficient catalysts for converting CO2 into cyclic carbonates

Abstract: A series of hexanuclear 3d–4f complexes with unique structures as catalysts for CO2 fixation into cyclic carbonates under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Based on the recently reported mechanism of the cycloaddition of CO 2 and epoxides, [106][107][108] we explore and propose a…”
Section: Catalytic Propertiesmentioning
confidence: 99%
“…Based on the recently reported mechanism of the cycloaddition of CO 2 and epoxides, [106][107][108] we explore and propose a…”
Section: Catalytic Propertiesmentioning
confidence: 99%
“…Domino, Friedel-Crafts, Mannich, Michael addition and cross-coupling reactions have all been successfully catalyzed by polynuclear 3d-4f coordination clusters. 14,15 Enhanced CO 2 transformations by asymmetric Zn-Ln complexes, [16][17][18][19] and catalytic olefin hydrogenation promoted by Ni-Lu complexes-in which lanthanide coordination was crucial for tuning and exploiting the reactivity at the Ni centerhave also been reported in the last five years. 20 Lanthanides incorporated into Mn-based water oxidation cluster mimics modulate the Mn potentials, as well as the O-atom transfer activities of these systems.…”
Section: Introductionmentioning
confidence: 95%
“…Catalysis involving 3d–4f complexes also is a quickly developing field; lanthanides can have a marked effect on both small molecule and organometallic reactions. Domino, Friedel–Crafts, Mannich, Michael addition, and cross-coupling reactions have all been successfully catalyzed by polynuclear 3d–4f coordination clusters. , Enhanced CO 2 transformations by asymmetric Zn–Ln complexes and catalytic olefin hydrogenation promoted by Ni–Lu complexesin which lanthanide coordination was crucial for tuning and exploiting the reactivity at the Ni centerhave also been reported in the past five years . Lanthanides incorporated into Mn-based water oxidation cluster mimics modulate the Mn potentials as well as the O-atom transfer activities of these systems. , The first examples of molecular 3d–4f water oxidation catalysts (WOCs), a Co 3 Ln (Ln = Ho–Yb) cubane series reported by Evangelisti et al, also showed enhanced photocatalytic performance compared to Co-only molecular WOCs …”
Section: Introductionmentioning
confidence: 96%
“…The IR spectrum of 2 confirmed that the structural integrity of 2 was well maintained after catalysis (Figure 2b). The cycle of the catalytic system was successfully repeated seven times with little change in conversion (Figure 2a The recyclability and stability of a catalyst plays an integral role in practical application [24,28,29]. The recycling experiment was carried out by the optimal reaction conditions obtained under the above experiment, i.e., 60 °C and 10 bar of CO2 and 12 h. 1 mol% of the catalyst and propylene oxide were placed in an autoclave and passed through 10 bar of CO2 for 12 h to calculate the yield.…”
Section: Catalytic Activity For Co 2 Fixationmentioning
confidence: 99%